2021
DOI: 10.3389/fmicb.2021.734780
|View full text |Cite
|
Sign up to set email alerts
|

Establishing an Efficient Genetic Manipulation System for Sulfated Echinocandin Producing Fungus Coleophoma empetri

Abstract: Micafungin is an important echinocandin antifungal agent for the treatment of invasive fungal infections. In industry, micafungin is derived from the natural product FR901379, which is a non-ribosomal cyclic hexapeptide produced by the filamentous fungus Coleophoma empetri. The difficulty of genetic manipulation in C. empetri restricts the clarification of FR901379 biosynthetic mechanism. In this work, we developed an efficient genetic manipulation system in the industrial FR901379-producing strain C. empetri … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…However, in their research, the efficiency of gene editing was not studied. Recently, Men et al reported protoplast-mediated transformation, and this method was used to achieve the disruption of the melanin gene . In their study, the gene disruption efficiency was only 4%, which demonstrated a low efficiency of the traditional gene editing method in C.…”
Section: Introductionmentioning
confidence: 99%
“…However, in their research, the efficiency of gene editing was not studied. Recently, Men et al reported protoplast-mediated transformation, and this method was used to achieve the disruption of the melanin gene . In their study, the gene disruption efficiency was only 4%, which demonstrated a low efficiency of the traditional gene editing method in C.…”
Section: Introductionmentioning
confidence: 99%
“…All of the expression cassettes were individually introduced into C. empetri MEFC09 through (PEG)-CaCl 2 -mediated protoplast transformation [ 34 ]. Transformants were selected on PDAS plates amended with 100 mg/L hygromycin B and verified by genomic PCR.…”
Section: Methodsmentioning
confidence: 99%
“…The putative function of the predicted enzymes was confirmed with the online NCBI BLASTP programmer ( http://blast.ncbi.nlm.nih.gov ). Gene disruption was carried out via homologous recombination as described previously [ 34 ]. To knock out the CEfks1 gene, approximately 1.2 kb of 5' and 3' DNA of the CEfks1 gene were amplified by PCR from the genome of C. empetri MEFC09 using the primer pairs UCEfks1-F/UCEfks1-R and DCEfks1-F/DCEfks1-R and were fused with the marker hph by fusion PCR.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The fungi Coleophoma cylindrospora or Coleophoma empetri F-11899 produces the NRP acylated to fatty acid, coded as FR901379 (16) . This sulfated echinocandin is a precursor of the partial chemical synthesis of the echinocandin, micafungin, commercially sold as Mycamine and Fungiguard [ 103 ]. Recently, the BGCs involved in the biosynthesis of FR901379 (16) were analyzed and an efficient clustered regularly interspaced short palindromic repeats/Cas9-based gene editing tool for the industrial production strain C. empetri SIPI1284 was established [ 104 ].…”
Section: Bioactive Fungal Secondary Metabolites and Derivatives Succe...mentioning
confidence: 99%